Factors Related to Father’s Behavior in Preventing Childhood Stunting Based on Health Belief Model - Eka Mishbahatul Mar’ah Has; Candra Panji Asmoro; Wilhelmus Petrus Gua (Jurnal Keperawatan Indonesia, 2022)
Childhood stunting is still a significant public health burden in Indonesia. Fathers' engagement in childcare could improve a child's health and help to prevent stunting. This study aimed to analyse factors related to the father's behaviour in preventing childhood stunting based on Health Belief Model. This study was used a correlational study design with a cross-sectional approach. This study involved 199 fathers who had children under five years old, recorded at Puskesmas (Public Health Center) Maronggela, East Nusa Tenggara, Indonesia. Samples were taken using the cluster random sampling technique. The independent variables were the father's perceived susceptibility, perceived severity, perceived benefit, perceived barrier, cues to action, and self-efficacy regarding childhood stunting and its prevention. The dependent variable was the father's behaviour in preventing childhood stunting. The questionnaire was used to collect the data. Data were then analysed using the Spearman Rho Test with a level significance of 95% (α < 0.05). The statistical analysis showed that perceived susceptibility (p = 0.023; r = 0.161) and cues to action (p = 0.004; r = 0.204) correlated with the father's behaviour in preventing childhood stunting, while perceived severity, perceived benefits, perceived barriers, and self-efficacy did not correlate. The current study suggests that fathers' behaviour to prevent stunting among children under five years was related to their perception of an illness and the cues that can trigger their decision-making process. These findings can be used to arrange health promotion programs to improve fathers' behaviour and engagement in childcare to prevent childhood stunting. Keywords: childhood stunting, early life nutrition, father, health belief model, preventive behaviour Abstrak Faktor-faktor yang Berhubungan dengan Perilaku Ayah dalam Mencegah Stunting Pada Balita Berdasarkan Health Belief Model. Stunting pada balita masih menjadi beban kesehatan masyarakat yang signifikan di Indonesia. Keterlibatan ayah dalam pengasuhan balita dapat meningkatkan kesehatan balita dan membantu mencegah stunting. Penelitian ini menganalisis faktor-faktor yang berhubungan dengan perilaku ayah dalam mencegah stunting pada balita berdasarkan Health Belief Model. Penelitian ini menggunakan desain penelitian korelasional dengan pendekatan cross sectional. Penelitian ini melibatkan 199 ayah yang memiliki balita, yang tercatat di Puskesmas Maronggela, Nusa Tenggara Timur, Indonesia. Variabel independen adalah kerentanan yang dirasakan ayah, keparahan yang dirasakan, manfaat yang dirasakan, hambatan yang dirasakan, isyarat untuk bertindak, dan self-efficacy berkaitan dengan perilaku pencegahan stunting pada balita. Variabel terikat adalah perilaku ayah dalam mencegah stunting pada balita. Kuesioner digunakan untuk mengumpulkan data. Uji Statistik dilakukan menggunakan Spearman Rho dengan signifikansi 95% (α < 0,05). Analisis statistik menunjukkan bahwa persepsi kerentanan (p = 0,023; r = 0,161) dan isyarat untuk bertindak (p = 0,004; r = 0,204) berkorelasi dengan perilaku ayah dalam mencegah stunting pada masa kanak-kanak, sedangkan persepsi keparahan, manfaat yang dirasakan, hambatan yang dirasakan, dan efikasi diri tidak berkorelasi. Studi saat ini menunjukkan bahwa perilaku ayah untuk mencegah stunting pada balita terkait dengan persepsi mereka tentang suatu penyakit dan isyarat yang dapat memicu proses pengambilan keputusan mereka. Temuan ini dapat digunakan untuk menyusun program promosi kesehatan untuk meningkatkan perilaku dan keterlibatan ayah dalam pengasuhan balita untuk mencegah pengerdilan anak. Kata Kunci: ayah, balita stunting, early life nutrition, health belief model, perilaku pencegahan